Characteristics, Diagnosis, Treatments and Public Awareness of Covid-19 Pandemic in Bangladesh: Mathematical Analysis (Bangladesh Journal of Infectious Diseases, 2022)
Background: The situation of Covid-19 in Bangladesh is analysed using a mathematical model.Objective: The objective of this study was the mathematical analysis and statistics of Covid-19 in Bangladesh which originates with reliable and perfect forecasts of the outbreak.Methodology: The Runge- Kutta method was applied to calculate the variables of the system of equations of the SEIRD compartmental model which was developed based on the SEIR model. Data of Covid-19 pandemic in Bangladesh were analyzed from March 08 to December 07, 2020.Results: The cumulative infection rate was used in the model to obtain the best fit with the available data. The statistics of Covid-19 in Bangladesh showed that the highest numbers of infections and deaths were observed in the 4th month (end of June) from the reported date those were consistent with other countries. We had also derived a reproduction number, Rt for each day so that the model’s result closely replicates the daily number of recently infected cases. Furthermore, the infected and death rate were observed highest among the age group of 31-40 and 61-above, respectively.Conclusion: This study contributes to a better understanding about the control policies of the Covid-19 pandemic in Bangladesh based on the estimated parameters of the proposed model and investigations of corona statistics.Bangladesh Journal of Infectious Diseases June 2021;8(1):18-26